Dignifying Children through Inclusive Childrens Literature - Fransisca Kristanti (Journal of Language and Literature, 2016)
Children with disabilities are often considered less capable than those without disabilities. In Indonesian childrens literature, disability is under-represented and the need to start representing disability in Indonesian childrens literature is pressing. Inclusive books imposing on the development of empathy leads to actions in dignifying children of all types, with or without disabilities. Some inclusive childrens literature worldwide set good examples of dignifying children. This paper tries to elaborate the urgency of having accessible inclusive childrens literature in Indonesia by collecting and presenting examples of inclusive childrens literature around the world which represents disabilities as diversities in society.